Development of HOTS Questions with Two-Level Multiple Choice Diagnostic Tests in Environmental Change Learning in Class X SMA/MA Students - Sibarani, Tohonan Yacob; Marianti, Aditya (Journal of Biology Education, 2022)
Education is an effort to develop the potential in students, the quality of education is determined by the quality of learning. The quality of learning in curriculum implementation aims to foster student character education with HOTS-based assessment (Higher Order Thinking Skill) or higher-order thinking skills that students must have in the 21st century. Students' higher-order thinking skills are analytical skills, analytical abilities can be identified by diagnostic tests . This study aims to develop HOTS items with a diagnostic test to identify students' analytical skills on environmental change learning for class X SMA/MA. The method used in this research is RnD (Research and Development) with a 4D model design including: Define, Design, Development and Desseminate. The subjects in this study were students of class XI and XII MIPA 1 and 2 SMA YSKI, Semarang for the academic year 2020/2021. Data was collected by observation, interviews and literature review. Data were taken from instruments which included: validation sheets, HOTS items with diagnostic tests to identify students' analytical skills, questionnaires for teacher and student responses. Data analysis includes content validation by experts, item validation with the help of Microsoft Excel and Rasch Model The student's analytical ability profile on the small-scale test is 44.8% and the large-scale test is 31.09%.